Pengembangan Learning Management System (LMS) Berorientasi Etnopedagogi untuk Meningkatkan Kemampuan Berpikir Kritis IPAS Siswa Sekolah Dasar di SDN 1 Bunkate - Lara Kariani; Ida Ermiana; Ibrahim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Abstrac: Ethnopedagogy has significant potential to enhance students’ critical thinking skills through the integration of local cultural values into the learning process. Critical thinking is an essential skill that needs to be developed in elementary school students, particularly in understanding science concepts such as matter and its changes. This study aims to develop an ethnopedagogy-oriented LMS (Learning Management System) to improve students’ critical thinking skills on the topic of matter and its changes in fourth-grade elementary school. The problem addressed in this study is the low level of students’ critical thinking skills, influenced by conventional teaching practices, limited use of innovative learning media, and the lack of integration of local cultural values in science (IPAS) learning. This study employed a R&D (Research and Development) method using the Alessi and Trollip model, which consists of planning, design, and development stages. The subjects of this study were fourth-grade elementary school students. The instruments used included expert validation sheets, response questionnaires, and tests (pre-test and post-test).The results showed that the LMS was categorized as highly feasible based on expert validation, with scores of 90% from material experts and 94% from media experts, as well as positive responses from teachers (96,7%) and students (96%). The LMS was also proven effective in improving students’ critical thinking skills, as indicated by an N-Gain score of 0.74 in the high category. Therefore, the ethnopedagogy-oriented LMS is feasible and effective as a learning media for science (IPAS) in elementary school